Double Fortified Salt in India: Coverage, Efficacy and Way Forward - Mannar, M.G. Venkatesh; Raman, J. K. (Indian Journal of Community Health, 2018)
Iron deficiency remains the world’s most widespread nutritional disorder and India is one of the countries very worst afflicted. India has successfully reduced the burden of iodine-deficiency disorders through mandatory iodization of salt for more than 20 years. This has resulted in a significant decrease in the prevalence of iodine deficiency diseases. Building on the success with iodization, double fortification of salt with iodine and iron is gaining ground and can be integrated with established iodization processes. DFS contemplates the creation and distribution of a powerful innovative product with demonstrated health effects, building on existing distribution platforms for salt through public distribution channels targeted to some of the most impoverished populations in the country at minimal expense and without requiring changes in cultural habits and compliance. Two formulations have been approved by Food Safety and Standard Authority of India (FSSAI) with iron either in the form of encapsulated ferrous fumarate or ferrous sulphate. A meta-analysis showed that DFS increased hemoglobin concentrations significantly. This intervention as part of a broader anemia strategy has the potential to effect large-scale anemia reduction across populations in India on a permanent and economically self-sustaining basis.